Peran Lumbrokinase pada Tata Laksana Stroke Iskemik - Mardiono, Marcellinus Michael Leonard (PT Kalbe Farma Tbk., 2024)
Stroke is a major cause of disability and cognitive impairment, accounting for 5.2% deaths worldwide. Antiplatelets and anticoagulants have been widely used as prevention of recurrent stroke. Recently, lumbrokinase has been used in stroke and other cardiovascular patients, but further research is needed.